2021
DOI: 10.1101/2021.05.07.443156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corticothalamic Projections Deliver Enhanced-Responses to Medial Geniculate Body as a Function of the Temporal Reliability of the Stimulus

Abstract: Aging and challenging signal-in-noise conditions are known to engage use of cortical resources to help maintain speech understanding. Extensive corticothalamic projections are thought to provide attentional, mnemonic and cognitive-related inputs in support of sensory inferior colliculus (IC) inputs to the medial geniculate body (MGB). Here we show that a decrease in modulation depth, a temporally less distinct periodic acoustic signal, leads to a jittered ascending temporal code, changing MGB unit responses fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 106 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Repetition enhancement has also been observed in the medial geniculate body in response to temporally degraded stimuli that are hypothesized to engage top-down resources to compensate for bottom-up acoustic information loss (Cai et al, 2016;Kommajosyula et al, 2019). Interestingly, this enhancement is reversed when cortico-thalamic pathways are blocked, further suggesting that repetition enhancement in the auditory system reflects a top-down phenomenon (Kommajosyula et al, 2021).…”
Section: Repetition Enhancement and Repetition Suppression In Icmentioning
confidence: 95%
“…Repetition enhancement has also been observed in the medial geniculate body in response to temporally degraded stimuli that are hypothesized to engage top-down resources to compensate for bottom-up acoustic information loss (Cai et al, 2016;Kommajosyula et al, 2019). Interestingly, this enhancement is reversed when cortico-thalamic pathways are blocked, further suggesting that repetition enhancement in the auditory system reflects a top-down phenomenon (Kommajosyula et al, 2021).…”
Section: Repetition Enhancement and Repetition Suppression In Icmentioning
confidence: 95%
“…However, repetition enhancement was observed in all three areas. Lesicko et al 2022 and Kommajosyula et al 2021 also found repetition enhancement in the IC and auditory thalamus of awake rodents, respectively. This is consistent with our findings that periodic target speaker sequences evoked stronger responses than random target speaker sequences (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, corticothalamic activation reduces adaptation to rapid repetitive stimulation as excitatory and inhibitory synaptic depression differs between the first-order visual/somatosensory thalamus and TRN (Mease et al, 2014;Crandall et al, 2015). In the auditory thalamus, corticothalamic activity seems to reduce adaptation to less-salient modulated noise since inactivation of corticothalamic neurons blocked the reduction (Kommajosyula et al, 2021). Therefore, corticothalamic neurons may be helpful for maintaining precise temporal responses in sequential or rapidly fluctuating sounds, which is characteristic of music and speech, and especially in less-salient sounds.…”
Section: Temporal Representation and Precisionmentioning
confidence: 99%
“…We postulate that corticothalamic feedback benefits other aspects of auditory scene analysis too. For example, enhanced signal detection by corticothalamic feedback seems to be robust for less salient inputs (Happel et al, 2014;Kommajosyula et al, 2021). Corticothalamic feedback may also contribute to signalin-noise processing by amplifying weak foreground sounds by controlling the gain of MGBv neurons.…”
Section: Selective Elimination Of Corticothalamic Neuronsmentioning
confidence: 99%
See 1 more Smart Citation